Urgensi Guru BK Individual di Sekolah dalam Meningkatkan Percaya Diri Siswa di MAN 1 Medan - Rahmadana, Wulandari; Lubis, Wahyu Gunawan; Srinurdayang, Srinurdayang; Kamal, Arsyad; Saragih, Muhammad Putra Dinata (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Confidence is one of the things that is important for every individual, especially for students at school. Students who lack confidence will find it difficult to adapt to the existing environment at school. Therefore it is necessary to have follow-up from the school, namely by carrying out Guidance and Counseling teacher counseling services. This research is a type of qualitative research with a descriptive approach. Where the purpose of this research is to find out how the role of the counseling teacher plays in dealing with students who lack self-confidence. The subject of this research involves one of the counseling teachers. Data collection techniques used observation, interviews, sound recordings and documentation. From this study it was found that the method used was the face to face method, namely the individual technique of the counseling teacher directly calling the students concerned to come to the counseling room. By providing individual counseling so that students are more courageous in showing their abilities in front of their friends, and are not awkward in interacting with other Pongo pygmaeus. Basically a lack of self-confidence harms students not only through associating with a low rule attitude, but through students considering their choices in a different way. Lack of self-confidence may require attention to help ensure that students' future choices are not unnecessarily limited. Keywords : Confidence, Individual Counseling, Student.